Victim–Offender Mediation and Reduced Reoffending: Gauging the Self-Selection Bias: - Jonas-van Dijk, Jiska (Crime & delinquency, 2020)
Previous research suggests that participation in victim-offender mediation (VOM) can lower the risk of reoffending. However, no randomized controlled trials have been done to examine this effect of VOM. Given that participation in VOM is voluntary, previous studies likely suffer from self-selection bias. To address this bias, we compared reoffending rates of three different offender groups: offenders who participated in VOM; offenders who were willing to participate, but whose counterpart declined VOM; and offenders unwilling to participate (total N = 1,275). Results replicated that participation in VOM predicts lower reoffending rates and suggested that this effect is not solely due to a self-selection bias. Suggestions are made for future research to examine why VOM causes lower reoffending rates.